NEW INSIGHTS IN ENVIRONMENTAL AND SUSTAINABLE ETHICS - Vicini, Andrea (Asian Horizons, 2012)
In his 2012 book, Learning from the Octopus: How Secrets from Nature Can Help Us Fight Terrorist Attacks, Natural Disasters, and Disease, Rafe Sagarin turns to nature and to some of its phenomena to gather insights on contemporary questions that challenge us ethically, like security strategies.1 Trained as a marine ecologist, in 2002 Sagarin was working as a science adviser for a member of the American Congress, when issues of national and global security needed to be addressed urgently and effectively after September 11, 2001. In his volume, he describes how living beings face environmental risks, threats, and challenges. The octopus, for example, with its eight tentacles, blends into the background and each tentacle has the ability of choosing which type of camouflage is more appropriate. Safety is provided by a decentralized and extremely adaptable system. As a consequence, readiness and preparedness is increased.